Independence of judiciary in Slovenia - Zajc, Katarina (Acta Histriae, 2014)
The article examines the independence of judiciary in Slovenia since its secession from Yugoslavia and communist regime in 1991. Using the theory on the independence of judiciary and the Landes - Posner model of judicial independence the article concludes that there are two possible conclusions as to why the legislative and executive branches were encroaching the independence of judiciary via wages. One is the lack of political competition which gives the other two branches the chance to control judiciary and the other one is that the encroachment of judiciary independence via wages was not intentional and does not have any negative impact on Slovene judiciary, which needs to be further examined empirically in the future work.
Keywords: independence; sodstvo; judges; neodvisnost sodstva; judiciary; pravosodje; wages; sodniki; plače; political competition; politična konkurenca; Slovenia; Slovenija